2018
DOI: 10.1055/s-0038-1673699
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Function of Women with Infertility

Abstract: Objective To assess the sexual function, anxiety, and depression of infertile women relative to a control group. Methods Infertile women (infertile group, IG) of reproductive age were invited to participate in this controlled study. A control group (CG) of women was recruited from the general population of the same city. Sexual function was assessed by the Female Sexual Function Index (FSFI), and anxiety and depression were measured by the Hospital Anxiety and Depression Scale (HADS). R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 30 publications
0
6
0
1
Order By: Relevance
“…A study by Salomao et al ( 22 ) showed that infertile women do not have higher sexual dysfunction in comparison to the women without infertility, but women with more anxiety or depression showed more sexual dysfunction. It is not known, however, whether women experience sexual dysfunction due to infertility or depression or if stress following infertility can cause sexual dysfunction.…”
Section: Discussionmentioning
confidence: 98%
“…A study by Salomao et al ( 22 ) showed that infertile women do not have higher sexual dysfunction in comparison to the women without infertility, but women with more anxiety or depression showed more sexual dysfunction. It is not known, however, whether women experience sexual dysfunction due to infertility or depression or if stress following infertility can cause sexual dysfunction.…”
Section: Discussionmentioning
confidence: 98%
“…Esse desbalanço hormonal pode acarretar distúrbios sexuais e psicológicos importantes, agravando o problema de inf ertilidade e disf unção sexual que já existe nos casais com dif iculdade de concepção natural. A duração da inf ertilidade aumenta o risco de disf unção sexual f eminina e de distúrbios psiquiátricos nesses indivíduos (SALOMAO PB, et al, 2018) Os painéis genéticos são os testes mais utilizados hoje em dia para determinar causas genéticas de inf ertilidade. A escolha de quais genes buscar nesses painéis depende do médico especialista em f ertilidad e. Ainda há uma necessidade crescente de novas pesquisas na área para descrever a causalidade entre os achados e a inf ertilidade em si, porém observa-se a evolução constante nesse tipo de pesquisa (OKUTMAN O, et al, 2018).…”
Section: Métodosunclassified
“…(87.5% vs 69.8%). Salomăo et al 2018 [ 31 ] Case–control study 140 140 FSFI HADS N.A N.A N.A Infertile women had no increased risk of SD with respect to controls. Anxiety and depression increased the risk of SD.…”
Section: Infertility and Sexual Functionmentioning
confidence: 99%
“…With respect to fertile female populations, case–control studies showed conflicting results. Some studies found no differences in the prevalence of FSD in infertile women, as compared to fertile controls [ 31 – 34 ]. In two studies conducted on a Turkish population, despite no differences in FSD prevalence between infertile and fertile women, the prevalence of FSD was very high [ 35 , 36 ].…”
Section: Infertility and Sexual Functionmentioning
confidence: 99%